Pemberian Ekstrak Fermentasi Tanaman (FPJ) Terhadap Pertumbuhan Dan Hasil Tanaman Sawi Pakcoy Menggunakan Metode Korean Natural Farming (KNF) - Hidayat, Asngat; Sutoko, N. Adi; Arini Al Ifah (JURNAL ILMIAH AGRINECA, 2024)
This research aims to determine the effectiveness of administering fermented plant juice (FPJ) based on the basic ingredients and solubility levels on the growth of pakcoy mustard greens. This research was carried out from 9 April 2021 to 20 June 2021 in Penulih Suroyudan, Sukoharjo, Wonosobo Regency, Central Java. This research used a completely randomized design (CRD) with one factorial and one control unit with 3 replications. Factor 1 is the basic ingredients for making FPJ, namely bamboo shoots and water spinach and the second factor is the solubility level, namely 1:500ml, 1:800ml, 1:1000ml water. Components of observing plant growth include plant height, number of leaves, leaf area, root length, and plant fresh weight. Research data was analyzed for variance using the One-way F 5% ANOVA test and DMRT at 5% level using the IBM SPSS application. The results showed that there was a significant influence on the growth of plant height and number of leaves at plant age 28 and 36 days after planting and root length growth at plant age 36 days after planting. The treatment of FPJ bamboo shoots with a solubility of 1:800 and 1:1000 ml of water gave the best effect on the growth of pak choy mustard plants.